1997
DOI: 10.1159/000196661
|View full text |Cite
|
Sign up to set email alerts
|

Modafinil in Obstructive Sleep Apnea-Hypopnea Syndrome: A Pilot Study in 6 Patients

Abstract: We studied the effects of modafinil, a vigilance-enhancing drug, on excessive daytime sleepiness, memory, night sleep and respiration in 6 patients with obstructive sleep apnea-hypopnea syndrome (OSAHS) using a double-blind random cross-over design with 24-hour polysomnography, verbal memory test and a 5-week sleep-wake diary kept by the patients. There were two 2-week treatment periods in which either modafinil or placebo was used; they were separated by a 1-week wash-out period. Our results show that modafin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(20 citation statements)
references
References 7 publications
1
19
0
Order By: Relevance
“…The abnormal insulin resistance and change in glucose metabolism during sleep linked to obesity [16], is an important problem when studying neuronal activity (or its resultant, the sleep EEG). In subjects with upper airway dysfunction, it has been shown that certain obese patients, despite appropriate treatment with nasal continuous positive airway pressure, may present with residual sleepiness and may require prescription of a stimulant [17,18]. Undoubtedly, some patients with UAR pattern can be obese [19], but the known physiological impact of android obesity on diaphragm position and changes in ventilation/perfusion during REM sleep muscle atonia are factors that led us to select a nonobese population.…”
Section: Discussionmentioning
confidence: 99%
“…The abnormal insulin resistance and change in glucose metabolism during sleep linked to obesity [16], is an important problem when studying neuronal activity (or its resultant, the sleep EEG). In subjects with upper airway dysfunction, it has been shown that certain obese patients, despite appropriate treatment with nasal continuous positive airway pressure, may present with residual sleepiness and may require prescription of a stimulant [17,18]. Undoubtedly, some patients with UAR pattern can be obese [19], but the known physiological impact of android obesity on diaphragm position and changes in ventilation/perfusion during REM sleep muscle atonia are factors that led us to select a nonobese population.…”
Section: Discussionmentioning
confidence: 99%
“…To date, modafinil has been shown to facilitate wakefulness in patients with narcolepsy (Boivin et al 1993;Billiard et al 1994;Besset et al 1996;Broughton et al 1997;US Modafinil in Narcolepsy Multicenter Study Group 1998Mitler et al 2000;Moldofsky et al 2000), and obstructive sleep apnea/hypopnea syndrome (Arnulf et al 1997;Cassel et al 1998;Pack et al 2001). In addition to improving wakefulness, modafinil has been shown significantly to improve overall clinical condition (US Modafinil in Narcolepsy Multicenter Study Group 1998 and health-related quality of life (Beusterien et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…To date, modafinil has been studied in two small pilot trials in patients with OSA/HS (43,44), albeit with different doses and designs from those of the present study. Both studies showed that modafinil improved daytime wakefulness but had no significant effect on sleep-disordered breathing or resting blood pressure monitored during the day.…”
mentioning
confidence: 99%